Milk Pasteurization with Geothermal Energy - Lund, John W. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1997)
Milk pasteurization with geothermal energy has been viewed by the author in two locations in the world: Klamath Falls, Oregon and Oradea, Romania. The former is no longer in operation; but, the latter has been operating since 1981. A third dairy using geothermal energy has been reported in Iceland which was established in 1930 to pasteurize milk and evaporate whey to produce brown whey cheese. This dairy merged with another co-op dairy in 1938 and was shut down. A description of the first two of these installations is deemed important, as there is potential for similar installation in other geothermal locations